Potensi Pengembangan Kawasan Berbasis Transit Oriented Development di Sekitar Titik Transit Kabupaten Bogor: The Potential of Transit Oriented Development at Transit Nodes in Bogor Regency - Nedalia Wilza; Ernan Rustiadi; Janthy Trilusianthy Hidajat (P4W LPPM IPB, 2021)
The high number of commuters in Bogor Regency has triggered the development of settlements at transit areas. In addition, Bogor Regency is also connected to rail-based mass public transportation in the Jabodetabek area which supports the mobility of its population. This study aims to identify the suitability of a transit area to be developed with Transit Oriented Development (TOD) concept. The research location is among the transit areas of two intercity train stations and seven existing urban commuter line train stations in Bogor Regency. Observations focused on the area in a radius of 800 meters from the station which is assessed as the maximum distance a person can walk for 15 minutes. Potential locations are determined by the AHP (Analytical Hierarchy Process) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method on several variables that form the ideal TOD. The variables observed include aspects of transportation and aspects of land use which are derived into several indicators. Based on the research, it was found that the most potential area to be developed with the TOD concept is the transit area of Cibinong station, followed by transit areas of Bojonggede station, Citayam station, and Cilebut station. Meanwhile, transit areas of Parung Panjang station and Tenjo station have medium potential, and transit areas Maseng Station and Cigombong Station are not potential.